2014
DOI: 10.1111/sms.12201
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac output during exercise: A comparison of four methods

Abstract: Several techniques assessing cardiac output (Q) during exercise are available. The extent to which the measurements obtained from each respective technique compares to one another, however, is unclear. We quantified Q simultaneously using four methods: the Fick method with blood obtained from the right atrium (Q(Fick-M)), Innocor (inert gas rebreathing; Q(Inn)), Physioflow (impedance cardiography; Q(Phys)), and Nexfin (pulse contour analysis; Q(Pulse)) in 12 male subjects during incremental cycling exercise to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 51 publications
(60 reference statements)
7
72
0
Order By: Relevance
“…The data presented here are consistent with previous studies that have reported lower cardiac output from the inert gas rebreathing when compared with other non‐invasive cardiac output measuring devices, that is pulse contour analysis, (Bartels, ; Siebenmann, ). This is probably due to recirculation of N 2 O, which reduces alveolar‐arterial diffusion gradient for N 2 O and further attenuate N 2 O uptake (Bartels, ).…”
Section: Discussionsupporting
confidence: 91%
“…The data presented here are consistent with previous studies that have reported lower cardiac output from the inert gas rebreathing when compared with other non‐invasive cardiac output measuring devices, that is pulse contour analysis, (Bartels, ; Siebenmann, ). This is probably due to recirculation of N 2 O, which reduces alveolar‐arterial diffusion gradient for N 2 O and further attenuate N 2 O uptake (Bartels, ).…”
Section: Discussionsupporting
confidence: 91%
“…The method has previously been validated showing a day-to-day reproducibility of 4.3% (18) and that the measured Q values are accurate compared with the direct Fick method (7). In our experience the Innocor tends to underestimate Q and that this is most likely due to an overlap in recirculation of the inert gas if multiple measurements are performed (55). In the current study the rebreathings were separated by several minutes with the intent to eliminate potential effects of recirculating inert gas.…”
Section: Methodsmentioning
confidence: 90%
“…Given that there is no effect for menstrual cycle phase or indeed OCP use on SV, alternate explanations are sought. A possibility for the rising and highly variable results reported by Wang and colleagues (Wang et al ., ) could be the approach used to estimate SV, single breath (SB) breathing procedure, a physically challenging procedure requiring the participant to perform a series of maximal expirations followed by maximal inspiration where the breath in a gas mixture of 0·3% of CO, CH 4 , C 2 H 2 , 21% O 2 in balanced nitrogen, and has been associated with increased variability when compared to less demanding methods (Siebenmann et al ., ). In the present study, the non‐invasive Physioflow ® thoracic impedance device was used, which has been shown to provide both valid and reliable results in the determination of SV and HR under both submaximal and maximal exercise conditions (Siebenmann et al ., ).…”
Section: Discussionmentioning
confidence: 97%